2010
DOI: 10.1093/hsw/35.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Older Latinos' Attitudes toward and Comfort with End-of-Life Planning

Abstract: The purpose of this study was to determine which of two educational interventions delivered in Spanish would influence Latino elders' attitudes toward and comfort with end-of-life planning in comparison with a control group receiving only standard information routinely provided. Using a posttest-only control group design, elders receiving home care services who agreed to participate were randomly assigned to one of three groups: Conversación A; Conversación B, with culturally relevant material added; and a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Other interventions aimed to improve understandings of and influence attitudes towards EoL care were through culturally-tailored material for family members and older persons approaching EoL [ 110 – 113 ]. Culturally-tailored print and online resources (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Other interventions aimed to improve understandings of and influence attitudes towards EoL care were through culturally-tailored material for family members and older persons approaching EoL [ 110 – 113 ]. Culturally-tailored print and online resources (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, efforts to increase knowledge about end-of-life care options will need to be sensitive to language barriers and require clear communication when (7) 11 (7) 13 (8) 6 (5) 18 (9 using translators. [34][35][36][37] It is also possible that consideration of health literacy and/or access to Latino providers could enhance communication of and education about hospice. 34,38 However, our result that knowledge was not independently related to intentions to use hospice suggests that translation and communication of information is important but not sufficient to increase access of Latinos to hospice care.…”
Section: Discussionmentioning
confidence: 99%
“…Given the likelihood that economic circumstances will result in the family's inability to care for their older relatives, cultural protocols have subtly changed the ways in which Hispanics define care obligations in the face of economic vulnerability. For example, there has been a shift away from the obligation of adult children caring for their parents to the obligation of ageing parents to not be a burden to their children (Heyman and Gutheil 2010). Recent scholarship has found that the direction of dependence is shifting downwards as more Hispanic adult children are dependent on ageing parents (Treas 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, adult children may worry that such conversations would make their parents anxious by "tempting fate" (Gutheil and Heyman 2006). Resistance to address end of life, fatalism, and a strong belief that God and prayer will provide for the well being in later life can deter difficult conversations between generations such as will and testament preparations (Edgell and Docka 2007;Herrera et al 2009;Tait et al 2011, Heyman andGutheil 2010). As a result, research shows that, compared to other ethnic and cultural groups, Hispanics are the least informed about long-term health care issues and end-of-life planning (Caralis et al1993;Delgadillo et al 2004).…”
Section: Literature Reviewmentioning
confidence: 99%